T-shirt preference of grade 6 female students from the University of the Philippines Integrated School, University of the Philippines, Diliman, Quezon City - Talosig, Gianna Mae P.; Escano, Maria Monica R. (2003.)
T-shirts are used by almost everyone no matter how young or how old. This is perhaps because of its simplicity and the comfort of wearing it. According to Blair (1992), in the knitted apparel industry, the knit T is the most popular among the knit shirts. A local study made by Campo (1990) and Escano (1998) found out that children, as early as 3 have already developed a preference in clothing. Campo's study revealed that children from 6-12 years old value the style, color and fit of garments according to that order, style given the most importance. This study aimed to find out the T-shirt style preference of grade six girls from the University of the Philippines Integrated School. It sought to answer the following problems: (1) What type of T-shirts do young girls prefer to wear? (2) What are the garment details of the T-shirts that they have? (3) Do they prefer the garment details that their T-shirts possess? Specifically this study was conducted to: (1) determine the T-shirt preference of the grade six schoolgirls in terms of selected T-shirt clothing style features - T-shirt shape and length, neckline, sleeve type, and hem shape; (3) correlate the T-shirt styles that the grade six girls prefer and the T-shirt styles that they possess. Data from this study were obtained through the use of a questionnaire designed and distributed by the researcher herself. A census or 100% sampling was conducted with 78% response rate was conducted. There were 45 of the 58 grade six girls from UPIS who participated in this study. Statistical tools were utilized such as frequency distribution, means, rank orders and bar charts to analyze and summarize the data. The Pearson product-moment correlation coefficient was used to compute for the correlation of the variables T-shirt styles preferred and T-shirt styles owned. To test the significance, t-test was used. After the data were collected and analyzed, the results show that the respondents like both the tubular and shaped T-shirt shapes; the straight hem; T-shirt lengths falling from the first hips below; the round, V-shape, keyhole and funnel necklines; and the plain, raglan, cap, roll and bell sleeve types. These styles also generally dominate the girls' T-shirt wardrobe. On the other hand, the styles that they dislike are T-shirts that have waistline level lengths, U shaped neckline and petal, cape and puff sleeve types. These are styles least present in their wardrobe. It was also found that there exists a strong positive correlation between the T-shirt style preference of the girls and the T-shirt styles that they own.
Thesis (BS Clothing Technology)--University of the Philippines Diliman.
Keywords: T-shirts.; Consumer preferences